1997
DOI: 10.1111/j.1365-2591.1997.tb00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological findings and clinical treatment procedures in endodontic cases selected for microbiological investigation

Abstract: The relationship between bacteriological findings and clinical treatment procedures was investigated in root canal treatment cases that were selected for bacteriological investigation by general dental practitioners in Finland. The cultures were sent to the Oral Microbiological Service Laboratory at the Institute of Dentistry in Helsinki. Two groups of teeth were selected based on the type of infection present in the root canal system. The 'enteric bacteria' group consisted of 40 sequential cases where Enteroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
133
1
30

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(170 citation statements)
references
References 15 publications
6
133
1
30
Order By: Relevance
“…6 The most common reason for the failures in conservative root canal therapy are problems in instrumentation, however, occasionally bacteria resistant to conservative therapy of good quality may also be involved. 7 Hence, a threedimensional seal with the antimicrobial property of the sealer is critical for endodontic success. It is generally believed that the significant cause of root canal treatment …”
Section: Discussionmentioning
confidence: 99%
“…6 The most common reason for the failures in conservative root canal therapy are problems in instrumentation, however, occasionally bacteria resistant to conservative therapy of good quality may also be involved. 7 Hence, a threedimensional seal with the antimicrobial property of the sealer is critical for endodontic success. It is generally believed that the significant cause of root canal treatment …”
Section: Discussionmentioning
confidence: 99%
“…"Bacteria-associated endodontic failures together with pulp-periapical infections refractory to conventional treatment represent the unresolved bacteriological problems in endodontics" (2). Numerous studies have shown that persistent endodontic infections are often caused by Enterococcus faecalis (1,3).…”
mentioning
confidence: 99%
“…However, occasionally, bacteria resistant to conservative therapy may also be involved (1). "Bacteria-associated endodontic failures together with pulp-periapical infections refractory to conventional treatment represent the unresolved bacteriological problems in endodontics" (2).…”
mentioning
confidence: 99%
“…It has been shown that EF rarely appears in primary endodontic lesions [28]. However, some have documented its occurrence in primary as well as secondary endodontic lesions [1,29].…”
Section: Resultsmentioning
confidence: 99%